Canine Neutrophil Extracellular Traps Enhance Clot Formation and Delay Lysis. Issue 1 (January 2018) - Jeffery, Unity; LeVine, Dana N.
Autoimmune diseases increase the risk of thrombosis. Neutrophil extracellular traps (NETs) are webs of DNA and protein that may mediate thrombosis in autoimmune diseases. Human and murine studies show NET-releasing neutrophils within a thrombus promote its growth, but it is unclear to what extent NET fragments released into circulation during inflammation are prothrombotic. This study hypothesized that canine NETs promote clot formation and impair lysis even in the absence of neutrophils. NETs were prepared from PMA-stimulated neutrophils and added to fibrinogen and thrombin or to recalcified pooled canine platelet-poor plasma, tissue factor, and tissue plasminogen activator. Clot formation and lysis were measured spectrophotometrically. NETs did not alter fibrin clot formation, but NETs increased maximum clot formation velocity ( P = .001) and delayed lysis ( P = .009) of plasma clots compared with supernatants from nonstimulated neutrophils. DNase digestion of NETs reduced their effect on clot lysis but not maximum clot formation velocity. This suggested impaired lysis was principally mediated by DNA within NETs but that NET proteins were principally responsible for increased speed of clot formation. Previous reports suggested elastase or histones might be responsible for the effect of NETs on clot formation. Elastase activity was greatly reduced by plasma, and addition of histones to plasma did not increase formation velocity, suggesting these proteins were not responsible for increasing maximum formation velocity. This study showed that NETs enhanced clot formation and impaired clot lysis in canine platelet-poor plasma. These in vitro findings suggest both NET proteins and DNA may contribute to thrombosis in inflammatory disease.